2004
DOI: 10.1177/000312240406900203
|View full text |Cite
|
Sign up to set email alerts
|

What is Originality in the Humanities and the Social Sciences?

Abstract: International audienceDrawing on interviews with peer-review panelists from five multidisciplinary fellowship competitions, this paper analyzes one of the main criteria used to evaluate scholarship in the humanities and the social sciences: originality. Whereas the literature in the sociology of science focuses on the natural sciences and defines originality as the production of new findings and new theories, we show that in the context of fellowship competitions, peer reviewers in the social sciences and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
184
0
19

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(207 citation statements)
references
References 29 publications
4
184
0
19
Order By: Relevance
“…The published literature addresses only some of these topics. Thurmair (1992, 1995) report on the properties of reviews as a type of text; Guetzkow, Lamont, and Mallard (2004) investigate the usage of originality as a quality criteria; and Hartmann and Neidhardt (Neidhardt 1988;Hartmann and Neidhardt 1990;Hartmann 1990) provide a content analysis of reviews from the procedures of the German Research Foundation (Deutsche Forschungsgemeinschaft, DFG) by identifying a set of eleven quality criteria. Since a search for literature on the subject yielded only these publications as relevant a short summary and discussion of each of them will be presented.…”
Section: Science Funding and The Content Of Reviewsmentioning
confidence: 99%
“…The published literature addresses only some of these topics. Thurmair (1992, 1995) report on the properties of reviews as a type of text; Guetzkow, Lamont, and Mallard (2004) investigate the usage of originality as a quality criteria; and Hartmann and Neidhardt (Neidhardt 1988;Hartmann and Neidhardt 1990;Hartmann 1990) provide a content analysis of reviews from the procedures of the German Research Foundation (Deutsche Forschungsgemeinschaft, DFG) by identifying a set of eleven quality criteria. Since a search for literature on the subject yielded only these publications as relevant a short summary and discussion of each of them will be presented.…”
Section: Science Funding and The Content Of Reviewsmentioning
confidence: 99%
“…The literature so far describes the characteristics of SSH research in the following way: a) SSH research is interpretative, that is, humanities research is mainly text-and theory-driven and social sciences are more concept-driven, while the natural sciences set up their studies to answer specific questions and are progress-driven (MacDonald, 1994;Guetzkow et al, 2004;Lamont, 2009); it is reflective and introduces new perspectives in academia, by fostering discursive controversy and competing visions (Fisher et al, 2000;Hellqvist, 2010). With regard to the society, they bring a decisive contribution to the training of critical thinking as a prerequisite for democracy (Nussbaum, 2010) or to the critical examination of modern trends, such as technologisation (Luckmann, 2004); c) it is mainly individual (Finkenstaedt, 1990;Weingart et al, 1991), few publications are co-authored (Hemlin, 1996;Hellqvist, 2010) and research is often connected to the person conducting it (Hemlin and Gustafsson, 1996;Guetzkow et al, 2004); d) productivity is not that important for research performance in the SSH (Hemlin, 1993;Fisher et al, 2000;Hug et al, 2013); e) societal orientation is important, i.e. research is meant to influence society, direct interaction with society is part of SSH research (Weingart et al, 1991;Hellqvist, 2010;Hug et al, 2013); but f) the influence of society or other stakeholders outside of academia, such as external funding, on SSH research is evaluated negatively (Hemlin, 1993;Hug et al, 2013;Ochsner et al, 2013).…”
Section: Ssh Research Practices and Criteria For Research Qualitymentioning
confidence: 99%
“…A more descriptive approach was chosen by Guetzkow, Lamont and Mallard (2004). They analysed interviews with peer review panellists from multidisciplinary fellowship competitions and found that originality was the most frequently mentioned criterion for judging applications.…”
Section: Ssh Research Practices and Criteria For Research Qualitymentioning
confidence: 99%
“…However, it did not find fertile ground in analytical and language-centred AngloAmerican philosophy. Lamont analyses the difference between the two national academic contexts, both in regards to accepted epistemological styles, modes of knowledge circulation and institutional organization (Guetzkow, Lamont, and Mallard 2004;Knorr Cetina 1999).…”
Section: The Principle Of Contextualismmentioning
confidence: 99%